FAKTOR-FAKTOR PENYEBAB RENDAHNYA MINAT PETANI UNTUK MENERAPKAN BUDIDAYA CABAI MERAH RAMAH LINGKUNGAN DI KABUPATEN LAMPUNG SELATAN - Puji Astuti; R. Hanung Ismono; Suriaty Situmorang (Lampung University, 2013)
This research aimed to analyze the causal factors on Farmers Low Interest to Implement theEnvironmentally Friendly Red Chili Farming In South Lampung Regency. This research employed a surveymethod by using constructed quisionairs. The research samples were 71 farmers, drawn from nonenvironmentallyfriendly red chilli farmers. The research was conducted in five districts of South LampungRegency, namely Natar, Way Sulan, Candipuro, Kalianda and Penengahan. The data was analyze byanalysis factors of SPSS program. The result showed that there were three factors causing farmers lowinterest to implement environmentally friendly red chilli farming. They were cultivation application and theofficer guidance, means and pest attact, in addition to cultivation result.